Revisión de las tecnologías para tratamiento de aguas de producción petrolera para su aprovechamiento en el riego de cultivos (2021)
The research focused on the review of production water treatment technologies for use in crop irrigation. Initially there was an overall characterization of the components that production water may have, among which are inorganic ions, dissolved total solids, organic constituents, hydrocarbons in oil, metals, radioisotopes and added chemicals. In addition, the parameters that a water should have for crop irrigation were determined, the most relevant and that have the most involvements in cultivation and soil are: salinity, sodicity, alkalinity, pH and toxicity by specific ions.